Degradation of Toxic Indigo Carmine Dye by Electrosynthesized Ferrate (VI) - Barisci, S.; Inan, H.; Turkay, O.; Dimoglo, A.; Erol, D. (Journal of Applied Solution Chemistry and Modeling, 2017)
Response surface methodology was applied for optimizing indigo carmine (IC) dye removal by electrochemically produced ferrate (VI). Box-Behnken design was employed in this study, and design parameters were pH, Fe (VI) dose and initial dye concentration (Co). R2 and adjusted R2 values were very high that indicated very good accuracy for the employed model. Optimum operational conditions were: 4.08-7.69 for pH, 24-118.83 mg/L for Fe (VI) dose and 60.68-99.13 mg/L for complete removal of IC. Produced by electrochemical method Ferrate (VI) provides high effectiveness for IC dye-containing synthetic wastewater.